The Circular Economy Recent Advances in Sustainable Waste Management - Zhang, Tao (IntechOpen, 2022)
The treatment of waste is highly relevant to human life and is receiving increasing attention from researchers. This volume contains a number of innovative and cutting-edge approaches to waste treatment, which hopefully will provide authors with new ideas for research in the area of waste treatment to contribute to the development of circular economy models.